Factors predicting compliance with the official COVID-19 health guidelines - Milošević Đorđević , Jasna; Kljajić, Duško; Đurić, Živojin (Sociološki pregled, 2021)
Although the development of vaccines against COVID-19 may mark the rounding of the corner in the pandemic, several issues are delaying our exit out of it. The majority of people seem to be concerned about the vaccines and unwilling to take them, while also not being responsible enough when it comes to the rest of the guidelines. In this paper, we wanted to examine the levels of support for different official guidelines, as well as the reasons behind their rejection. In the representative study (N=1198) of Serbian adults (aged 18+) conducted in September 2020 we found that most people do comply with guidelines such as hand washing and mask-wearing, but do not want to be vaccinated. We also found that conspiracy beliefs, trust in science and institutions, and health risk perception all play an important role in predicting guidelines compliance along with vaccination intentions. Path analysis confirmed that conspiracy belief indirectly predicts health guidance compliance, lowering health risk perception and trust in science and institutions.